Report from the European Myeloma Network on interphase FISH in multiple myeloma and related disorders - Ross, Fiona M.; Neben, Kai (Haematologica, the hematology journal, 2012)
The European Myeloma Network has organized two workshops on fluorescence in situ hybridization in multiple myeloma. The first aimed to identify specific indications and consensus technical approaches of current practice. A second workshop followed a quality control exercise in which 21 laboratories analyzed diagnostic cases of purified plasma cells for recurrent abnormalities. The summary report was discussed at the EHA Myeloma Scientific Working Group Meeting 2010. During the quality control exercise, there was acceptable agreement on more than 1,000 tests. The conclusions from the exercise were that the primary clinical applications for FISH analysis were for newly diagnosed cases of MM or frank relapse cases. A range of technical recommendations included: 1) material should be part of the first draw of the aspirate; 2) samples should be sent at suitable times to allow for the lengthy processing procedure; 3) most importantly, PCs must be purified or specifically identified; 4) positive cut-off levels should be relatively conservative: 10% for fusion or break-apart probes, 20% for numerical abnormalities; 5) informative probes should be combined to best effect; 6) in specialist laboratories, a single experienced analyst is considered adequate; 7) at least 100 PC should be scored; 8) essential abnormalities to test for are t(4;14), t(14;16) and 17p13 deletions; 9) suitable commercial probes should be available for clinically relevant abnormalities; 10) the clinical report should be expressed clearly and must state the percentage of PC involved and the method used for identification; 11) a retrospective European based FISH data bank linked to clinical data should be generated; and 12) prospective analysis should be centralized for upcoming trials based on the recommendations made. The European Myeloma Network aims to build on these recommendations to establish standards for a common European data base to define subgroups with prognostic significance.
Gesehen am 24.04.2018